2020
DOI: 10.3389/fmicb.2020.537290
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Growth of Staphylococcus aureus Under High Glucose Conditions Is Associated With Decreased Pentaglycine Expression

Abstract: The high-glucose-induced cytotoxicity in diabetes has been widely recognized. Staphylococcus aureus is the most frequent pathogen isolated from diabetic foot ulcers, but the properties of this bacterium under high glucose conditions remain unclear. S. aureus grew in medium usually forms weak biofilm, and which was significantly increased by addition of glucose. However, extracellular DNA (eDNA), an important component of biofilms, was markedly decreased in presence of 15 mM glucose. The reduced eDNA content wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 44 publications
(55 reference statements)
1
12
0
Order By: Relevance
“…(67,68) However, E. coli and P. aeruginosa may grow better in high glucose conditions than Staphylococcus aureus and commensal Staphylococcus epidermidis. (69) The downregulation of this T1R3 cilia pathway by P. aeruginosa flagellin-TLR5 signaling (reducing T1R3 ASL glucose (which was not certified by peer review) is the author/funder. All rights reserved.…”
Section: Discussionmentioning
confidence: 99%
“…(67,68) However, E. coli and P. aeruginosa may grow better in high glucose conditions than Staphylococcus aureus and commensal Staphylococcus epidermidis. (69) The downregulation of this T1R3 cilia pathway by P. aeruginosa flagellin-TLR5 signaling (reducing T1R3 ASL glucose (which was not certified by peer review) is the author/funder. All rights reserved.…”
Section: Discussionmentioning
confidence: 99%
“…Internal sugars are primarily used for glycolysis, biosynthesis of various components, such as cell walls and lipoteichoic acid, and intercellular polysaccharide biosynthesis. However, high-sugar environments also tend to inhibit the growth of staphylococci ( Luo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, genes SAOUHSC_00707, SAOUHSC_01807, SAOUHSC_02402 and SAOUHSC_02403 up-regulated by SprC, as shown in Supplementary Table 2 , might result in an increased expressions of β-D-fructose 1, 6-bisphosphate and enhanced glycolysis ( Deng et al, 2014 ; Gong et al, 2017 ; Li et al, 2018 ; Chen et al, 2019 ). Luo et al demonstrated that the growth rate of S. aureus was reduced under high glucose conditions due to impairment of the pentaglycine bridge contributing to the bacterial cell wall structure ( Luo et al, 2020 ). Therefore, SprC might provide one approach to maintain cell stability by increasing the expression of genes related to upgraded glycolysis.…”
Section: Discussionmentioning
confidence: 99%